KONTRIBUSI GURU BIMBINGAN KONSELING DALAM MENGATASI PROBLEMATIKA BELAJAR SISWA SMK NEGERI 3 KOTA KENDARI - Faizah Binti Awad (Institut Agama Islam Negeri Kendari, 2015)
AbstractProblems of learning is the obstacles and distractions, even make difficult for students to achieve learning goals. Problems of learning does not stand alone but always highly correlated wit h other things, such as biological, psychological and social aspects. Problems of learning often faced by the students require the contributions from teacher of counseling and guidence(BK) to solve it. From the result of study at SMK 3 Kota Kendari, was found that problems of learning are caused by: 1. The friendship relationship among students, 2. the relationship between students and parents, 3. the relationship between students and teachers, 4. economic factors; 5. domicile factors; and 6. the habit of getting up in the morning. Source of data analysis which is uses a qualitative descriptive, show thatcounseling and guidance teachers has applicative contribution through some kinds of communication relationship, namely: a. build communication between counseling and guidance teachers and school staff, b. build communication between counseling and guidance teachres and students, and c. building a harmonious communication between teachers and parents. Key words: problems of learning, counseling and guidanceAbstrakProblematika belajar merupakan hambatan dan gangguan, bahkan dapat mempersukar usaha peserta didik untuk mencapai tujuan belajarnya. Problematika belajar juga t idak berdiri sendiri akan tetapi senant iasa sangat berkaitan dengan hal-hal lainnya, seperti aspek biologis, psikologis dan sosial. Problematika belajar yang sering dihadapi peserta didik menuntut kontribusi guru Bimbingan Konseling (BK) dalam memecahkan problemdimaksud. Dari hasil penelit ian di SMK 3 Kota Kendari, diperoleh bahwa problematika belajar disebabkan oleh: 1. hubungan pertemanan antar peserta didik, 2. hubungan peserta didik dengan orang tuanya, 3. hubungan peserta didik dengan guru, 4. faktor ekonomi, 5. faktor domisili, dan 6. kebiasaan bangun pagi. Sumber data penelit ian yang menggunakan jenis diskriptifkualitatif ini menuturkan bahwa guru BK telah berkontribusi secara aplikatif melalui beberapa bentuk hubungan komunikasi, yaitu: a. membangun komunikasi antar guru BK dengan personel sekolah, b. membangun komunikasi antar guru BK dengan peserta didik, dan c. membangun komunikasi yang harmonis antar guru dengan orang tua peserta didik. Kata Kunci : Problematika Belajar, bimbingan dan konseling